2011
DOI: 10.1002/jcp.22701
|View full text |Cite
|
Sign up to set email alerts
|

Myocilin, a glaucoma-associated protein, promotes cell migration through activation of integrin-focal adhesion kinase-serine/threonine kinase signaling pathway

Abstract: The MYOCILIN gene encodes a secreted glycoprotein which is highly expressed in eye drainage structures. Mutations in this gene may lead to juvenile open-angle glaucoma and adult onset primary open-angle glaucoma, one of the leading causes of irreversible blindness in the world. Functions of wild-type myocilin are still unclear. We have recently demonstrated that myocilin is a modulator of Wnt signaling and may affect actin cytoskeleton organization. Here we report that myocilin and its naturally occurring prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…We found that myocilininduced muscle hypertrophy involves activation of the Akt signaling pathway and in this respect is more similar to insulin-like growth factor-1-induced skeletal myotube hypertrophy (56). Extracellular myocilin may serve as a modulator of Wnt signaling (22) and possess an ability to activate the integrin-FAK-PI3K-Akt signaling pathway (58). Because myocilin is not secreted from muscle cells, we believe that activation of the Akt signaling pathway in transgenic mice occurs mainly through the action of intracellular myocilin.…”
Section: Discussionmentioning
confidence: 66%
“…We found that myocilininduced muscle hypertrophy involves activation of the Akt signaling pathway and in this respect is more similar to insulin-like growth factor-1-induced skeletal myotube hypertrophy (56). Extracellular myocilin may serve as a modulator of Wnt signaling (22) and possess an ability to activate the integrin-FAK-PI3K-Akt signaling pathway (58). Because myocilin is not secreted from muscle cells, we believe that activation of the Akt signaling pathway in transgenic mice occurs mainly through the action of intracellular myocilin.…”
Section: Discussionmentioning
confidence: 66%
“…The function of MYOC is not clear but it may play a role in cell-extracellular matrix interactions (Goldwich et al, 2009; Peters et al, 2005), cell migration (Kwon and Tomarev, 2011) and mitrochondrial function (Sakai et al, 2007). In skeletal muscle, MYOC is part of the dystrophin-associated protein complex by binding α1-syntrophin and may play a role as a regulator of muscle hypertrophy pathways (Joe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular myocilin may serve as a modulator of Wnt signaling by interacting with several components of the Wnt signaling pathway (29). It may also increase cell migration by acting through the integrin-focal adhesion kinase signaling pathway (49). We showed that myocilin is expressed in MSCs, and the addition of extracellular myocilin enhances osteogenic MSC differentiation (44).…”
Section: Discussionmentioning
confidence: 89%
“…In our previous study, we demonstrated that EGF receptor phosphorylation was enhanced by treatment with a myocilin-containing medium (50). Myocilin may also activate focal adhesion kinase and its downstream phosphatidylinositide 3-kinase (PI3K) signaling pathway (49). Focal adhesion kinase-mediated activation of the PI3K pathway is able to stimulate the Raf/MEK/ERK signaling cascade via activation of p21-activated protein kinases (54,55).…”
Section: Discussionmentioning
confidence: 99%